Solguden and Other Stories. Hamsun, Ibsen and Forgery - Giuliano D’Amico (Edda)
Abstract The article analyzes a case of forgery, which included false documents by Henrik Ibsen and Knut Hamsun, that was debated in court in 2012. The study is based on a number of documents and materials to which the author was given access by Norwegian authorities. Arguing that literary forgeries not only are legal evidence, but also can have historical and aesthetic value, the article discusses what kind of documents were forged, what they tell us about Ibsen’s and Hamsun’s position in today’s literary canon, and how literary history would have changed if these documents had been proven authentic.